ANALISIS MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTU LIVEWORKSHEET PADA PEMBELAJARAN IPA DI KELAS VI SDN TAMBAKREJO 01 KOTA SEMARANG - Novi Istiqomah; Joko Sulianto; Aryo Andri Nugroho; J. Sustaminawhanti (STKIP Subang, 2023)
The purpose of this study was to analyze the Implementation of Learning with problem-based models, to describe the implementation of problem-based models assisted by Liveworksheet in science learning, and to describe the responses of students while participating in learning with problem-based models assisted by Liveworksheets in Science learning in class VI of SDN Tambakrejo 01. This research using descriptive qualitative method. The subjects of this study were students of class VI at SDN Tambakrejo 01. Sources of data were obtained from interviews, documentation, observation and questionnaires. The results of this study revealed that the teacher had implemented all the stages or steps of the problem-based learning model, namely: orienting students to problems, organizing students to learn, guiding individual and group investigations, developing and presenting work, as well as analyzing and evaluating problem-solving process with the help of the Liveworksheet application.